Targeting-intratumoral-lactic-acidosis transcatheter-arterial-chemoembolization for non-islet cell tumor hypoglycemia secondary to a liver metastatic solitary fibrous tumor: A case report and literature review - Jin, Kai; Zhong, Shan; Lin, Liya; Wu, Jianjun; Wang, Yuqi; Cui, Weijuan; Gu, Wei; Chao, Ming; Song, Xiaoxiao (Frontiers in Endocrinology, 2022)
Doege–Potter syndrome is a rare, paraneoplastic syndrome characterized by non-islet cell tumor hypoglycemia secondary to a solitary fibrous tumor. Doege–Potter syndrome always presents with recurrent fasting hypoglycemia, which can occasionally be life-threatening. The best choice of treatment for Doege–Potter syndrome and solitary fibrous tumor is complete resection. However, when it is unfeasible, local-regional treatment can be used as a palliative therapy. Herein, we report a case of a 46-year-old man with Doege–Potter syndrome that occurred secondary to liver and pancreatic metastatic solitary fibrous tumor. After he received 6 times targeting-intra-tumoral-lactic-acidosis transcatheter-arterial-chemoembolization (TILA-TACE) treatment in our hospital, his hypoglycemia was clinically cured, and the liver metastatic tumor was well controlled. We suggest that TILA-TACE can be considered when curative resection is unfeasible for metastatic liver solitary fibrous tumors, to help patient get further surgery opportunity.